Odpowiedzi

2009-12-21T17:19:53+01:00
0,05x + 0,04y = 46 / * (-4)
0,04x + 0,05y = 44 / * 5

-0,2x -0,16y = -184
0,2 + 0,25 = 220
------------------------

0 + 0,09y = 36
0,09 y = 36
y = 400

0,05x + 0,04y = 46
y = 400

0,05x + 0,04 * 400 = 46
y = 400

0,05x = 46 - 16
y = 400

x = 600
y = 400



Po lewej str. powinny być klamerki


Najlepsza Odpowiedź!
2009-12-21T17:23:42+01:00
X- I liczba
y- II liczba

5%x+4%y=46
4%x+5%y=44

0,05x+0,04y=46
0,04x+0,05y=44

0,05x=46-0,04y /:(0,05)
0,04x+0,05y=44

x=920-0,8y
0,04(920-0,8y)+0,05y=44

x=920-0,8y
36,8-0,032y+0,05y=44

x=920-0,8y
-0,032y+0,05y=44-36,8

x=920-0,8y
0,018y=7,2 /:(0,018)

x=920-0,8y
y=400

x=920-0,8*400
y=400

x=920-320
y=400

x=600
y=400

POZDRAWIAM :)